2022
DOI: 10.1108/ijm-06-2021-0331
|View full text |Cite
|
Sign up to set email alerts
|

High-performance work system and knowledge hoarding: the mediating role of competitive climate and the moderating role of high-performance work system psychological contract breach

Abstract: PurposeHigh-performance work system (HPWS) has been verified as a promoter of both organizational and individual outcomes. However, this research takes the conflicting view of HPWS to examine the impact of HPWS perception on knowledge hoarding. In addition, competitive climate is proposed to mediate the relationship while HPWS psychological contract breach is hypothesized to moderate the HPWS-knowledge hoarding linkage.Design/methodology/approachA quantitative research design is adopted with data collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
(161 reference statements)
1
7
0
Order By: Relevance
“…Indeed, employees who possess knowledge that others in the organization do not have are more likely to retain authority, power and influence (Muqadas et al, 2017). Moreover, scholars suggest that knowledge hoarding falls in the category of employee withdrawal behavior (Huy, 2023), and it is not uncommon for employees to engage in such behaviors under adverse circumstances, especially when there is a fear of career harm (Seitz et al, 2000). Hence, we propose the following hypothesis.…”
Section: Fear Of Career Harm and Knowledge-hoardingmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, employees who possess knowledge that others in the organization do not have are more likely to retain authority, power and influence (Muqadas et al, 2017). Moreover, scholars suggest that knowledge hoarding falls in the category of employee withdrawal behavior (Huy, 2023), and it is not uncommon for employees to engage in such behaviors under adverse circumstances, especially when there is a fear of career harm (Seitz et al, 2000). Hence, we propose the following hypothesis.…”
Section: Fear Of Career Harm and Knowledge-hoardingmentioning
confidence: 97%
“…For instance, Yang et al (2022) have examined the role of Machiavellianism as a facilitator of employee knowledge-hoarding behavior. Huy (2023) has found that high-performance work systems and competitive climate foster employee knowledge hoarding. We posit that another aspect of employees' lives that can play a crucial role in advancing the understanding of knowledge-hoarding behavior is their emotions.…”
Section: Knowledge Hoardingmentioning
confidence: 99%
See 1 more Smart Citation
“…Tran Huy ( 2022 ) stated it had been shown that HPWS benefits the results of both organizations and individuals. In contrast, this study adopts an opposing viewpoint of HPWS to investigate the influence that perception of HPWS has on the act of information hoarding.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Knowledge hoarding is believed to damage interpersonal relationships, creativity and innovation (Zhu et al , 2019) and impair information processing (Anaza and Nowlin, 2017). High-performance work systems increase employees’ knowledge hoarding behaviors with a competitive climate partially mediating the relationship (Huy, 2022. However, most research on the dysfunctional outcomes of knowledge hoarding has explicitly or implicitly used Evans et al (2015) definition that includes withholding of knowledge as an aspect of knowledge hoarding rather than Webster et al (2008) definition.…”
Section: Development Of Hypothesesmentioning
confidence: 99%